2005
DOI: 10.1111/j.1440-1843.2005.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exhaled nitric oxide and atopy in Asian young adults

Abstract: Increased FE(NO) levels are more reflective of atopy rather than asthma, and increased nitric oxide production may be predominantly a feature of atopy in asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
6
10
2
Order By: Relevance
“…Atopy was not an independent determinant for FeNO levels in our study population in contrast to the results of previous studies 21,22,29. A previous study with the Korean population conducted by Kim et al15 in indicated that atopy (alongside gender) is a significant predictor of FeNO levels.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Atopy was not an independent determinant for FeNO levels in our study population in contrast to the results of previous studies 21,22,29. A previous study with the Korean population conducted by Kim et al15 in indicated that atopy (alongside gender) is a significant predictor of FeNO levels.…”
Section: Discussioncontrasting
confidence: 97%
“…Travers et al21 suggested a mean FeNO of 17.9 ppb in healthy New Zealander adults (n=193, mean age=56.3±12.9, atopy rate=23.8%), and Olin et al28 showed a FeNO level of 16.6 ppb in healthy Swedish adults (n=1,131; mean age, 50.3±13.81; atopy rate, 25.3%). In Asia, Chng et al29 presented a median FeNO level of 38.4 ppb for atopic subjects and 15.7 ppb for non-atopic subjects in Singaporeans (n=45, mean age, 19.6; atopy rate, 61.8%); however, their subjects were younger than ours. We speculate that the reason for our lower FeNO ranges (than other ethnic groups) may be due to differences in living environment.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…A recent study from Taiwan involving 681 Asian children aged 5-18 years found that the geometric mean FeNO and the upper 95% CI were 13.7 and 29.7 ppb, respectively, and this was also higher when compared with the Caucasian population [30]. In fact, other smaller-scale studies involving Chinese and Korean adults also showed a similar level of FeNO value to our study (table 4) [25][26][27]. A study involving 895 African-Americans noted that the mean FeNO for males and females were 27¡26 ppb and 18¡18 ppb, respectively [31].…”
Section: Discussionsupporting
confidence: 86%
“…This factor might not be very significant as all current machines should follow the ATS/ERS guidelines [2,3] for calibration and maintenance. Conversely, a study from Singapore using the NIOX machine in testing 45 first-year Asian medical students and another study from Korea involving 166 adults aged 20-80 years using the same Sievers machine as in this study [26], found similar FeNO values to our study [25].…”
Section: Discussionsupporting
confidence: 79%